Effects of vibration training in interstitial lung diseases: a randomized controlled trial - Koczulla, Andreas Rembert; Kahn, Nicolas; Herth, Felix; Kreuter, Michael (Respiration, 2020)
Numerous studies have reported positive effects of exercise training in patients with interstitial lung disease (ILD) on physical capacity and quality of life. However, evidence is rare on the effects of specific forms of training and further pathophysiological mechanisms in these patients. Objectives: In this multicenter study we aimed to explore the clinical effects of whole-body vibration training (WBVT) in patients with ILD on various outcome measures, including proinflammatory cytokines and myostatin. Methods: We randomly assigned 26 patients with different forms of multidisciplinary confirmed fibrotic ILDs either to the WBVT group (n = 11; 55% male, 61 ± 14 years old, forced vital capacity 83.2 ± 29.3% predicted, 6-min walking distance [6MWD] 478 ± 79 m) performing 3 months of a standardized training (3 times per week), or to a control training group (CTG, n = 15; 60% male, 63 ± 9 years old, FVC 74.6 ± 20.5% predicted, 6MWD 455 ± 85 m) performing sham WBV training. Training in the two groups was performed on a GalileoTM vibration plate (6-20 vs. 5 Hz). The functional assessments before and after the intervention period included pulmonary function, 6MWD test, chair rise test, ultrasonographic measurement of quadriceps muscle thickness (cross-sectional area), quality of life questionnaires, and serum samples. Results: We observed a significant increase in 6MWD (∆Training = 30 m [12-67], p = 0.024) and a decrease of myostatin (∆Training = -465 pg/mL [-713 to -166], p = 0.008) in the WBVT group. In contrast, no significant differences were observed in the CTG. Conclusions: The present study demonstrates that WBVT is able to significantly increase 6MWD and decrease myostatin in patients with fibrotic ILDs. Therefore, WBVT seems to be a beneficial and feasible training modality in ILD patients. Clinical Trial Registry: German Clinical Trials Registry (DRKS00012930).
Gesehen am 21.10.2020